Ð¡Ð¾Ð²Ñ€ÐµÐ¼ÐµÐ½Ð½Ñ‹Ðµ Ð°ÑÐ¿ÐµÐºÑ‚Ñ‹ Ñ‚ÐµÑ€Ð°Ð¿Ð¸Ð¸ Ð²Ð¾ÑÐ¿Ð°Ð»Ð¸Ñ‚ÐµÐ»ÑŒÐ½Ñ‹Ñ… Ð·Ð°Ð±Ð¾Ð»ÐµÐ²Ð°Ð½Ð¸Ð¹ Ð¶ÐµÐ½ÑÐºÐ¸Ñ… Ð¿Ð¾Ð»Ð¾Ð²Ñ‹Ñ… Ð¾Ñ€Ð³Ð°Ð½Ð¾Ð² - Kuzmina, I. Yu. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2008)
The actual therapeutic protocols for female genital inflammatory diseases, stipulated by urogenital infections, have been studied. There was proved, that Genferon preparation together with the standard therapeutic means is well endured by patients, has a manifested immune-modulating effect, increases a therapeutic efficiency, decreases the pain syndrome with reduction of patients’ treatment terms, as well as decreases the probability of disease relapse occurrence.